RHODOCOCCAL PNEUMONIA IN IMMUNOCOMPROMISED PATIENTS: Wittane NA CHIANGMAI, Sanan SIMARAK - NA CHIANGMAI, Wittane; SIMARAK, Sanan (The ASEAN Journal of Radiology, 2023)
Rhodococcus equi is a recognised pulmonary pathogen in foals,swine, and calves. Most human infection have been associated with immune system dysfunction. We reported four patients with chest involvement from this organism.